The science book of motion - Ardley, Neil. (San Diego : Harcourt Brace Jovanovich, 1992)
Simple experiments demonstrate the laws of motion.
"Gulliver books.".
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
4.7
3-6
Keywords: Motion -- Experiments -- Juvenile literature; Motion -- Experiments; Experiments; Motion -- Experiments; Science -- Experiments; Motion -- Experiments; Integrated Ed -- Language arts -- Upper elementary